Riverbend Gap - Hunter, Denise, 1968- (Riverbend romance, 2021)
"From the bestselling author of The Convenient Groom (now a beloved Hallmark Original movie) comes the first romance in a brand-new series! When Deputy Cooper Robinson happens upon a car balanced on the edge of a cliff, he does everything he can think of to distract the distraught driver from her perilous situation-up to and including sharing things he's never disclosed to anyone. Likewise, an agitated Katie Loveland opens up to the deputy, and by the time she's rescued, she's formed an intense bond with the man. The traumatic accident makes Katie late to her first dinner with her boyfriend's family. Only then does she discover that the charming deputy who saved her life is also her boyfriend's brother. In the aftermath, both Katie and Cooper must decide what to do with their newfound vulnerability and emotional connection . . . And the decision they make could change everything"--